Aqueous microdroplets containing only ketones or aldehydes undergo Dakin and Baeyer–Villiger reactions. Issue 48 (25th November 2019) - Gao, Dan; Jin, Feng; Lee, Jae Kyoo; Zare, Richard N.
Abstract : The Dakin and Baeyer–Villiger (BV) oxidation reactions require addition of peroxides as oxidants and an acid or a base as a catalyst. Abstract : The Dakin and Baeyer–Villiger (BV) oxidation reactions require addition of peroxides as oxidants and an acid or a base as a catalyst. Reaction times range from hours to days to obtain target products. Previously, we reported that hydrogen peroxide (H2 O2 ) is spontaneously generated in water microdroplets without any added chemicals or applied electrical potential. Here, we report that the Dakin and BV reactions occur in modest yields within milliseconds in aqueous microdroplets at room-temperature without the addition of external peroxides and catalysts. H2 O2 generation is the result of the special environment of the microdroplet surface, which promotes water autoionization. We find that increasing the content of water and decreasing the droplet size improve the product yield of the Dakin and BV reactions, supporting the contention that the amount of H2 O2 generated in aqueous microdroplets could induce the two reactions and the reactions occur at or near the air–water interface of the microdroplet surface.